Direct synthesis of electrowettable nanostructured hybrid diamond. Issue 32 (30th July 2019) - Deshmukh, Sujit; Sankaran, Kamatchi Jothiramalingam; Banerjee, Debosmita; Yeh, Chien-Jui; Leou, Key-Chyang; Phase, Deodatta Maheshwar; Gupta, Mukul; Lin, I.-Nan; Haenen, Ken; Roy, Susanta Sinha; Waghmare, Prashant R.
Abstract : A low-voltage wetting transition from the Cassie–Baxter state to the Wenzel state was achieved by preparing a needle-like conductive diamond–graphite core–shell nanostructure. Abstract : The possibilities of precise control over the wetting characteristics of carbon-based hybrid nanostructures consisting of both sp 2 and sp 3 hybridized carbons using the electrowetting technique were demonstrated. An excellent polarity-dependent electrowetting behavior in the presence of an electrolyte followed an abrupt transition from the highly hydrophobic (contact angle ∼ 142°) Cassie–Baxter states to a hydrophilic (∼30°) Wenzel state, where diamond films acted as the anode. In addition, we also reported a remarkable transition from weakly hydrophobic to nearly superhydrophobic diamond nanostructures by chemical and morphological manipulations. The unique structural properties with precisely tailored morphology and surface roughness enabled such transitions on the nanostructured surface. This approach of preparing environmental stable hydrophobic surfaces with polarity-dependent wetting and precise control of the wetting mode transition could be used in numerous applications such as the electrochemical transport of liquids, supercapacitors, and low-friction microfluidics.